Humanitarian NGOs as instruments, partners, advocates and critics in the governance of international humanitarian response: complementary or conflicting roles?. Issue 1 (2nd January 2016) - Schwartz, Eric P.
Abstract : Non-governmental organisations (NGOs) play an important role in the governance of international humanitarian response as implementing partners to governments and international organisations, as advocates, and as critics. They face challenges in reconciling their role as implementing partner with their responsibility to promote principles of international humanitarianism, such as humanity, impartiality, neutrality and independence. But this tension can be managed to ensure effective assistance to those in need. Governments and international organisations should welcome the role of NGOs in the governance of humanitarian response, given the expertise and resources that NGOs provide. To improve integration of effort and overall effectiveness, governments and NGOs should work to establish greater communication and enhanced procedures for coordination, especially given the increased engagement by non-traditional donor governments in the provision of humanitarian aid.